Basic Shape dalam Desain Mebel Taman Bacaan Anak di Surabaya - Dominica Giovanna (Intra, 2017)
The establishment of the 'Taman Bacaan Anak' that becoming the trend nowadays, aimed to realize the city of Surabaya as literacy [7]. However, the "Taman Bacaan Anak" that is already exist, has not provided reading media that interest its visitors. Thus, the design of public facilities Poco Cocca (POCA) on "Taman Bacaan Anak" at Surabaya aims to accommodate the needs of a decent reading place for Surabaya citizens from various backgrounds, especially for children ages 4-10 years from middle to lower segment. Through the concept of "Adaptable Shape", POCA designed to increase children's reading interest in a fun way, which consists of 3 modular sets that based on 4 basic shape. In each set has 3 functions including work plane; sitting facilities; and storage. By the POCA's presence, hopefully can draw child's attention to create a comfortable and qualified learning. And also the children can stand the time during reading and motivated to interact with one another while around the area.